Estudo da dinâmica de acréscimo e perda de massa na estrela T Tauri clássica V354 Mon. - Nathalia Nazareth Junqueira Fonseca (2010)
The main goal of this work is to characterize the mass accretion and ejection processes of the classical T Tauri star V354 Mon, a member of the young stellar cluster NGC 2264. In March 2008, photometric and spectroscopic observations of this object were obtained simultaneously with the CoRoT satellite, the SOPHIE échelle spectrograph at the Observatoire de Haute-Provence (CNRS - France) and the 60 cm telescope at the Observatorio Pico dos Dias (LNA - Brazil) equipped with a CCD camera and Johnson/Cousins BV(RI)C filters. The light curve of V354 Mon shows periodical minima (p = 5,26 +- 0,50 days) that vary in depth and width at each rotational cycle. The BV(RI)C observations indicate that the system becomes slightly bluer as the flux increases. The spectra of this T Tauri star exhibit variable emission lines, with blueshifted and redshifted absorption components associated with a disk wind and with the accretion process, respectively, conformingthe magnetospheric accretion scenario. From the analysis of the photometric and spectroscopic data, it is possible to identify correlations between the emission line variability and the light curve modulation of the young system, like, for example, the occurrence of pronounced redshifted absorptions in the H alfa and H beta lines at the moments of minimumflux. This is an evidence that during photometric minima we see the accretion funnel projected on the stellar photosphere in our line of sight, implying that the hot spot coincides with the light curve minima. We applied models of cold and hot spots and a model of occultation by circumstellar material to investigate the source of the observed photometric variations. We conclude that material non-uniformly distributed in the inner part of the circumstellar disk is the main cause of the photometric modulation, which does not discard the presence of hotand cold spots at the stellar surface. It is believed that the distortion in the inner part of the disk is created by the dynamical interaction between the stellar magnetosphere, inclined with respect to the rotation axis, and the circumstellar disk, as also observed in the classical T Tauri star AA Tau and predicted by magneto-hydrodynamical numerical simulations.